Population activity of peach fruit fly Bactrocera zonata (Saunders) (Diptera: Tephiritidae) at fruits orchards in Kafer El-Shikh Governorate, Egypt - Khalil A. Draz; Reda M. Tabikha; Mohamed A. El-Aw, et al. (Arthropods, 2016)
Peach Fruit Fly (PFF) Bactrocera zonata (Saunders) is one of most dominant and destructive key pest in fruit orchards in different agro-ecosystem in Egypt, so monitoring adults' population fluctuation in orchards, through capturing adults, has been considered as main way to forecasting or management the pest. So current study aimed to assay the efficiency of Jackson traps baited with methyl eugenol (M.E.) on male capture, that were distributed in different fruit trees orchards, in different positions and hang levels in one of Egyptian agroecosystem (Kafer El-Shikh Governorate), from (May 2014 to April 2015). Moreover, adults capture in McPhail traps in navel orange orchards intercropping with Guava were exploded to detect abundant and rearing season of the pest studying impact of abiotic factors on population, and estimation number, time and duration of annual generation. Obtained results declared that the pest had 7-8 annually generation. Jackson traps that placed in center of orchard and hanged at 2 m height more efficient than others for male catches. Highest numbers of PFF male attack orchards of Navel orange intercropping with Guava, while the lowest were with Navel orange and Guava. Each of season and kind of orchard or intercropping system had combined and significant effect on mass trapping. In McPhail traps, highest mass trapping of adult was observed in autumn (20.353 adult/ trap/ week), while each of spring, summer and winter season were similar in mass trapping. Only Wind direction as climatic factors had negative significant effect on mass trapping of PFF adults in McPhail traps, while each of maximum and mean temperature of winter season had positive significant effect on mass trapping.